Biodegradation of Hydrocarbons by Bacillus cereus Isolated from Indoor and Outdoor Air of Selected Hospitals in Ilorin, Kwara State, Nigeria - D.O. Adetitun; R.B. Tomilayo; M.B. Oguntoye; A.A. Raheem (Journal of Applied Sciences and Environmental Management, 2020)
Indoor and outdoor air of five (5) hospitals in Ilorin, Kwara state were sampled using settling plate method to isolate fifteen (15) bacteria. Bacillus cereus was the identified spore former. Biodegradation performance of Bacillus cereus on hexadecane and heptane using Mineral Salts Medium  (MSM) was studied for 20 days at four days interval using the Jenway 6320D Spectrophotometer to assess the optical density. The degradation and utilization of the hydrocarbons occurred before the fourth day with readings for optical density obtained as 1.051nm and 0.820nm for hexadecane and heptane respectively. After day 4, there was a sharp decline in the utilization of hydrocarbons. A second experiment was setup for optical density with heptane and decane utilization being checked daily for a period of 5days. Bacillus cereus utilized the hydrocarbons till the fourth day as the optical density dropped on the fifth day. The readings for decane obtained on day 4 and day 5 were 0.431nm and 0.338nm respectively. Also, there was a decline in the readings of heptane from 0.451nm obtained on day 4 to 0.343nm obtained on day 5. This study shows that Bacillus cereus is promising in the biodegradation of alkanes and can also be utilized to clean up pollution from petroleum spill which is becoming a prevalent ecological hazard.